The application of PASS-computer program and molecular docking for the search of new anticonvulsants - Perekhoda, L (Annals of Mechnikov's Institute, 2020)
Introduction. Currently the priority goal of designing drugs is the integration of the methods of organic chemistry and pharmacology. The application of computer programmes which can predict interaction of potential drugs with molecules of biological targets makes possible to decrease the number of experiments on laboratory animals. Thereby the economic efficiency of production of new medicines increases. Models of the research the anticonvulsant activity (in particular, korazol, thiosemikarbazid, strychnine, etc.) are the most rigid experimental models of pharmacological screening, which basically entails the pains of laboratory animals or their death. The application of computer programmes in the research of potential anticonvulsants has economic and social desirability and high level of importance for the pharmaceutical science and health care. The most perspective methods of research are the virtual screening, molecular docking. These methods allow to evaluate the affinity of a substance to a specific biological target, i.e. to identify an inhibitor of a particular enzyme or protein. Material and methods. We have carried out the construction of 50 groups substances (507 hypothetical structures). We have chosen the five-membered di(three)azaheterocycle as basic pharmacophores to form virtual structures because firstly their structure is similar to cyclic conformation of neurotransmitter and secondly according to the literature perspective anticonvulsants had already found among these derivatives. Computer prediction of pharmacological activity for all compounds of virtual database was performed using the PASS (Prediction of Activity Spectra for Substances) computer programme. Results obtained by PASS-computer programme showed prospects of search the anticonvulsants among 10 groups of derivatives di(three)azaheterocycles (probable activity (Pa) of substances of these groups are from 0.5 to 0.84). In order to determine the potential anticonvulsant activity of 1,2,3(1,2,4)triazole, 1,3,4-oxa(thia)diazole we investigated the mechanisms of action that involve the interaction of the ligand NMDA-, GAMKA- or glutamate receptors and GABA-AT ligand-enzyme. We have perfomed docking research for our structures and for known anticonvulsants using the Fast Dock method, in which both protein and ligand are rigid (Software SCIGRESS; Fujitsu, Fukuoka, Japan). We have evaluated affinity of the investigated structures with molecules biotargets: GABAA receptor protein (PDB code 1GNU), glutamate receptor protein Glu-1 (PDB code 1EWK), GluN1 NMDA receptor protein (PDB code 3Q41) and protein enzyme GABA-AT (PDB code 1OHW). Results and discussion. As a result, we have obtained the values of scoring functions Consensus, which enabled to evaluate affinity compounds and biological anticonvulsant targets and identify 11 perspective groups of compounds (number of compounds 190) that can selectively inhibit NMDA, a GABA - or glutamate receptors and GABA aminotransferase enzyme in comparison with known anticonvulsant drugs. The number of active groups of the results PASS prediction according to the obtained results is 10 (the number of compounds 168). It should be noted that result of docking research coincided with the results of PASS prediction for eight groups of compounds. Conclusion. 1. Eleven groups of compounds derivatives of 1,2,3(1,2,4) -triazols, 1,3,4-oxadiazoles and 1,3,4- thiadiazoles was selected for further screening as perspective anticonvulsants; 2. GABA-ergic mode of action for 8 groups of derivatives and glutamatergic mode of action for 3 groups of derivatives five-membered di(three)azaheterocycle was predicted.